2020
DOI: 10.3390/ijerph17207374
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Upper-Body Exoskeletons on Human Metabolic Cost and Thermal Response during Work Tasks—A Systematic Review

Abstract: Background: New wearable assistive devices (exoskeletons) have been developed for assisting people during work activity or rehabilitation. Although exoskeletons have been introduced into different occupational fields in an attempt to reduce the risk of work-related musculoskeletal disorders, the effectiveness of their use in workplaces still needs to be investigated. This systematic review focused on the effects of upper-body exoskeletons (UBEs) on human metabolic cost and thermophysiological response during u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
19
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(24 citation statements)
references
References 68 publications
0
19
0
Order By: Relevance
“…Results indicated that an exoskeleton significantly reduced the required mechanical energy for tasks, which can help improve worker performance by reducing fatigue [ 6 ]. Based on a series of exoskeleton-based studies, researchers have demonstrated that this assistive-based technology improves both range of motion [ 16 , 17 ] and muscle fatigue or activation [ 16 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 ].…”
Section: Resultsmentioning
confidence: 99%
“…Results indicated that an exoskeleton significantly reduced the required mechanical energy for tasks, which can help improve worker performance by reducing fatigue [ 6 ]. Based on a series of exoskeleton-based studies, researchers have demonstrated that this assistive-based technology improves both range of motion [ 16 , 17 ] and muscle fatigue or activation [ 16 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 ].…”
Section: Resultsmentioning
confidence: 99%
“…Additionally, scientific reviews provide informative overviews of applied evaluations of either exoskeletal prototypes or commercial systems. For instance, they focus on the user's metabolic costs with upper-body exoskeletons [21] or muscular activity, body loading, and experience with trunk exoskeletons [22,23]. In contrast, Hoffmann et al [11] present a generic prevalence matrix of different applied types of analysis combined with their respective research objects for deriving patterns and best practices for prospective evaluation methodologies.…”
Section: Introductionmentioning
confidence: 99%
“…Instead of using EMG to measure the effects of upperextremity exoskeletons in the shoulders, physiological measures related to oxidative metabolism could provide a more appropriate picture of the potential of industrial exoskeletons to reduce occupational injury. A multitude of studies have explored the metabolic effects of both low back and upper-extremity exoskeletons, and a recent systematic review reports that the majority of these studies recorded significant reductions in the mean values of metabolic or cardiorespiratory parameters considered (Del Ferraro et al 2020). However, these studies measured global changes rather than localised metabolic changes occurring in the individual muscles of target body areas.…”
Section: Introductionmentioning
confidence: 99%